Detoxification of ochratoxin A and zearalenone by Pleurotus ostreatus during in vitro gastrointestinal digestion - Nobre, Clarisse (2022)
Supplementary data to this article can be found online at https://doi. org/10.1016/j.foodchem.2022.132525.